2013
DOI: 10.4236/ojml.2013.33035
|View full text |Cite
|
Sign up to set email alerts
|

Gender and the Communication of Gratitude in Jordan

Abstract: This paper examines Jordanians' perceptions of the ways and the extent to which gender influences the communication of gratitude in some everyday situations. The qualitative analysis of 20 interviews reveals a considerable influence of gender on the performance and reception of this communicative act. Differences between women and men were found in both same-gender and mixed-gender interactions in respect of the mandatoriness and the ways of communicating gratitude. The data show that Jordanian women appear to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The study revealed that diminutives are used in both positive and negative politeness contexts. Other studies focused on colloquial Jordanian Arabic such as Al-Qudah, 2017;Abushihab, 2015;Bani Mofarrej & Al-Abed Al-Haq, 2015;Al-Harahsheh, 2014, Almutlaq & Jarrah, 2013Al-Khawaldeh & Zegarac, 2013;Al-Sobh, 2013 andRababa'h &Malkawi, 2012. Some studies on politeness in Arabic focused on cultural aspects such as Samarah (2015) who studied politeness from a cultural perspective deriving examples mainly from Egyptian Arabic.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The study revealed that diminutives are used in both positive and negative politeness contexts. Other studies focused on colloquial Jordanian Arabic such as Al-Qudah, 2017;Abushihab, 2015;Bani Mofarrej & Al-Abed Al-Haq, 2015;Al-Harahsheh, 2014, Almutlaq & Jarrah, 2013Al-Khawaldeh & Zegarac, 2013;Al-Sobh, 2013 andRababa'h &Malkawi, 2012. Some studies on politeness in Arabic focused on cultural aspects such as Samarah (2015) who studied politeness from a cultural perspective deriving examples mainly from Egyptian Arabic.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The literature on this phenomenon is very rich. In Jordanian Arabic (henceforth, JA) many studies have been conducted in terms of speech acts aiming at establishing a kind of relation between them and some selected social variables (e.g., Al-Qudah, 2017;Abushihab, 2015;Bani Mofarrej & Al-Abed Al-Haq, 2015;Al-Harahsheh, 2014a;Almutlaq & Jarrah, 2013;Al-Khawaldeh & Zegarac, 2013;Al-Sobh, 2013;Rababa'h & Malkawi, 2012;Al-Momani, 2009, among others). As for the present study, it focuses on the differences in the expressions of requesting acts by Jordanian males and females found in their naturally-occurring interactions with the call-centre-customer service of a leading telecommunications company in Jordan.…”
Section: The Previous Studiesmentioning
confidence: 99%
“…Some of these studies investigated the strategies of thanking across cultures and within the same culture, and others focused on its functions. In the same fashion, a fair amount of research has tackled thanking in an Arab context (Al Khateeb, 2009;Al-Khawaldeh & Zegarac, 2013;Al-Momani et al, 2017;Morsi, 2010). However, the issue of responses to thanking has received little attention from both Arab and non-Arab scholars.…”
Section: Literature Reviewmentioning
confidence: 99%